ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL (RGEC) PADA BANK PEMBANGUNGAN DAERAH (BPD) PERIODE 2014-2016 - Sinaga, Rona Rosinta (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to determine the soundess of Bank Pembangunan Daerah (BPD) in the period of 2014-2016 using Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) method. The sample of this descriptive study is Bank Pembangunan Daerah with ROA and CAR of above BPD average in 2016. The data of this research are secondary, obtained from financial reports of the banks uses NPL and LDR ratio, Good Corporate Governance uses the banks’ self-assestment result, earnings uses ROA and NIM rations and Capital uses CAR. The results show that in the period 2014-2016, Risk Profile factor shows that the NPL of the banks below 5%. The LDR of most banks is 4, which is less sound. In the factors of earnings, the ROA of the banks more than 1,5 and the NIM is more than 5%, so the rating is 1, which is very sound. The capital factors shows that the bank’s CAR is more than 12%, which means that the bank is sound and able to fulfill the minimum capital requirements. Keywords : bank soundness, risk profile, good corporate governance, earnings, capital